2005
DOI: 10.1002/ajmg.a.30908
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 10 mosaicism and maternal uniparental disomy 10 in a liveborn infant with severe congenital malformations

Abstract: We report on a liveborn infant with trisomy 10 mosaicism combined with maternal uniparental heterodisomy for chromosome 10. The mosaicism 47,XY,+10/46,XY was found in five different tissues, including one blood sample, while cultured lymphocytes from two other blood samples showed a normal karyotype, 46,XY. DNA analysis with six PCR-based microsatellite markers demonstrated the trisomic cell line to be a result of maternal meiotic nondisjunction, and revealed maternal uniparental heterodisomy in the diploid ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Chromosome 11 duplications can be associated with renal malformations (2/17 11q23 to qter duplications present with renal malformations). Interestingly, Hahnemann et al (2005) reported a child with low level mosaic chromosome 10 trisomy, who in addition had preaxial polydactyly, blepharophimosis, microphthalmos, iris coloboma, cleft lip and palate and anal atresia. This baby died at 37 days of age.…”
Section: Clinical Reportmentioning
confidence: 99%
“…Chromosome 11 duplications can be associated with renal malformations (2/17 11q23 to qter duplications present with renal malformations). Interestingly, Hahnemann et al (2005) reported a child with low level mosaic chromosome 10 trisomy, who in addition had preaxial polydactyly, blepharophimosis, microphthalmos, iris coloboma, cleft lip and palate and anal atresia. This baby died at 37 days of age.…”
Section: Clinical Reportmentioning
confidence: 99%
“…Trisomy of chromosome 10 has been previously reported. 11 In addition, because the mother of our patient is more than 40 years old, and advanced maternal age increases the risk of trisomy, trisomic rescue would seem to be the more likely mechanism in our case. The formation of abnormal gametes in this case might have been the result of nondisjunction during meiosis I or during meiosis II.…”
Section: Discussionmentioning
confidence: 72%
“…Trisomy 10 is a rare lethal chromosomal abnormality, most frequently found in abortion products. Only six liveborn mosaic trisomy 10 infants, with severe malformations, dead in early infancy, have been reported [13]. A severe clinical syndrome can be defined, comprising ear abnormalities, cleft lip/palate, malformations of eyes, heart, and kidneys, and deformity of hands and feet and most often associated with death neonatally or in early infancy [13].…”
Section: Discussionmentioning
confidence: 99%